STROSSMAYEROV «KULTURI EKUMEIZAM» I EUROPA (Philological Studies, 2019)
The substance of ecumenism and a multicultural reality in South Slavic areas can be linked by starting from personal and other research on Strossmayer conducted till now and by observing him as an advocate of Croatian political goals, of Croatia's unity and independence (especially in national and supranational relations, “territorial integrity” and feudalism), of new research based on his texts, speeches and letters (of which many have their stylistic and literary value). Their substance can be linked through the way in which they can be analyzed today from a global ethics perspective (of Hans Küng), from contemporary ecumenism (of Pope John Paul II) and intercultural history and/or literary history. Special attention is given to questions of (Slavic) European integration, especially Europe’s South Slavic, «Turkish» part by interpreting Strossmayer's Memorandum to the Russian Government from 1876 in a broader sense. In conclusion, aspects of «cultural ecumenism», in Strossmayer's sense, are stressed through his need of expanding intercultural, inter-religious dialogue, including the appropriate intercultural, cultural and historical approaches and methods.